Spatial Conservation Prioritization for the Anuran Fauna of South America - Vasconcelos, Tiago S. [UNESP]; Silva, Fernando R. da; Santos, Tiago G. dos; Prado, Vitor H. M.; Provete, Diogo B.; Vasconcelos, TS; DaSilva, FR; DosSantos, TG; Prado, VHM; Provete, DB (Springer, 2019)
South America is the most biologically diverse continent on the planet, including anuran amphibians. However, the continent has been experiencing high levels of habitat degradation, and amphibians are considered the most endangered class of the vertebrate group globally. Therefore, the establishment of effective actions for the anuran protection in the continent is urgent. Here, we generate a spatial conservation prioritization of anurans in South America addressing different human-related and biological diversity metrics using the software MARXAN. We found that the anuran fauna of South America can be totally represented by the selection of similar to 19.53% of the total area of the continent. Contiguous selected areas are mainly located in the Tropical Andes and the Atlantic Forest coast. To a lesser extent, the selected areas can be also found in specific areas of Venezuela, the Brazilian Amazonian forest, and the temperate Chilean forests. In general, the contiguous areas represent forested areas within rough topographies of tropical countries and should be priority areas for anuran conservation in South America. Other areas within the tropical region, as well as in the southern temperate regions/countries, are less continuous and should involve more complex evaluations by decision-makers to foster reserve creation.
Keywords: Anura; Biological conservation; Conservation biogeography; MARXAN; Neotropics; Spatial prioritization